Analisis Prosedur Penyusutan Dokumen Rekam Medis di Puskesmas Rawat Inap di Kota - Retno Astuti Setijaningsih; Jaka Prasetya (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Public Health Center (PHC) is a central health development in its working area. The orientation of PHC is the patient safety, so medical records have to be kept safely in the appropriate order. Therefore, medical record documents can be traced easily and quickly. For maintaining medical records documents in a particular numbers in the spaces, it needs medical record documents retention to reduce the burden of storage and workload of file officer, that is associated with patient’s medical record documents tracking speed. There were some medical record documents missfile incidences due to stacking file.The research desain was a case study with cross sectional approach. Data was collected by observation and interviews and analyzed by descriptive analysis. The result showed that the numbering system that applied on the patient’s family folder was Unit Numbering System (UNS). Generally, PHCs implemented Terminal Digit Filing (TDF) system, but Puskesmas Tlogosari Kulon still applied Straight Numerical Filing (SNF). The retention system was decentralization, while Tlogosari Kulon implemented centralized. The retention of medical record documents was not scheduled routinely and there was no documentation. Several PHCs did not perpetuate medical record documents as regulated on The Permenkes Nomor 269/Menkes/PER/III/2008. Medical record documents retention required the disease index, patient index, standard operating procedure, record retentions schedules and documentation. In addition, it needs to reform the medical record documents management to facilitate the implementation of retention system.Keywords: medical record document, retention, public health center (PHC)